Fatores cr??ticos de sucesso em projetos de ERP cloud: uma an??lise quantitativa do cen??rio brasileiro - Gheller, Ang??lica Aparecida (2017)
The main objective of this research was to investigate the critical success factors for cloud ERP projects in the scenario of Brazilian companies. In addition, the secondary objectives were to identify the perception of benefits resulting from this implementation, in the aspect of improving organizational performance and the elaboration of a matrix to support the management of such projects, based on a review of the literature and the data collected from the field research. The method of the data collection was a self-directed questionnaire, and the statistical method was the canonical correlation, to answer the main research question. In addition, a factorial analysis and a multiple linear regression were run to investigate possible relationships between the independent variables (critical success factors) and the dependent variables (benefits) of the research model. The results obtained did not validate all the critical factors present in the literature, and those that were proven empirically were regrouped in new dimensions, being: security information and alignment of compliance, and communication and management of stakeholders.